PENGARUH VARIABEL-VARIABEL CORPORATE GOVERNANCE TERHADAP FINANCIAL DISTRESS (Studi Empiris pada Perusahaan di Sektor Industri Jasa Keuangan yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2022) - Anggraini, Aprilia Dwi; Cahyonowati, Nur (Diponegoro Journal of Accounting, 2024)
This study aims to examine the effect of corporate governance variables on financial distress. Corporate governance consists of internal mechanisms and external mechanisms. The internal mechanism consists of the Board of Directors, institutional ownership, managerial ownership, Independent Commissioner, and Audit Committee. Meanwhile, an example of an external mechanism is audit quality. The population in this study are companies in the Financial Services Industry sector listed on the Indonesia Stock Exchange from 2019 to 2022. Purposive sampling is the sampling method used in this study. The number of samples that fit the sample criteria and were used in this study were 77 samples. The data used in this study are secondary data in the form of company financial reports obtained through the Indonesia Stock Exchange website and the websites of each company. The hypothesis testing process in this study was carried out through the classical assumption test and hypothesis testing, namely the f test, t test, and the coefficient of determination test. The results of hypothesis testing in this study indicate that the board of directors, institutional ownership, independent board of commissioners, and audit quality have no effect on financial distress. Meanwhile, managerial ownership and audit committee have a negative effect on financial distress.